Electromechanical transient simulation model of low frequency flexible transmission system based on modular multilevel matrix converter. Issue 1 (1st December 2022) - Yang, Zedong; Hua, Wen; Lin, Jintian; Su, Zhida; Wang, Xueqiong; Tang, Yong
Abstract: Low frequency AC transmission has broad prospects in the future power system. How to establish its electromechanical transient simulation model and provide basic research means for its adaptability analysis after connecting to the large power grid is an urgent problem to be solved. Based on the existing electromechanical transient simulation methods, the mathematical model of modular multilevel matrix converter (M3C) is simplified, and an electromechanical transient simulation model composed of virtual DC circuit and equivalent AC circuit is proposed. On this basis, the power and voltage controller is designed according to the power decoupling characteristics of M3C. Further considering the operation requirements of the offshore wind power transmission system through low frequency AC transmission, an island control is designed to make M3C have the ability of passive control. Numerical examples verify the effectiveness of the proposed simulation model, which can effectively respond to short-circuit faults and power loss. This model can better meet the calculation requirements of large power grid simulation.